Water and climate: Recognize anthropogenic drought - AghaKouchak, Amir; Feldman, David; Hoerling, Martin; Huxman, Travis; Lund, Jay (Nature (London), 2015)
California's current extreme drought must be a lesson for managing water in a warmer, more densely populated world, say Amir AghaKouchak and colleagues.